Export instability and economic development - MacBean, Alasdair I. (London : Allen & Unwin, 1966)
This book examines the relative merits of different policies for dealing with the effect of export fluctuation on underdeveloped countries
Bibliography: p. 349-359.
oo 23/01/2019
Loans
Keywords: Commodity control; Economic development; Developing countries